A Study of the Challenges Faced by the Undergraduates in English Medium Education: A Study Based on First Year & Second Year Undergraduates at Uva Wellassa University - Dissanayake, D.M.R.N.; Abeyweera, G.H.; Samarasinghe, A.G.S.M.; Nayanahari, W.M.L.; Herath, H.M.D.N.; Silva, R.R.P. (University of Jaffna, 2025)
This study examines the challenges faced by undergraduates in an English medium learning environment and its impact on their academic performance. Language serves as a crucial medium for education. In many countries, including Sri Lanka, English is recognized as the second language. In most of the Sri Lankan universities, courses are conducted in the medium of English. This paper aims to investigate the challenging learning environment and the factors contributing to students’ inadequate language proficiency, which affects their academic performance. Both qualitative and quantitative data were collected through a questionnaire while a test covering their knowledge of grammar and writing was administered to first-year undergraduates from a sample of 389 students at Uva Wellassa University A questionnaire consisting of thirty-five questions was distributed among hundred second year undergraduates. The test was conducted simultaneous to the English Pre-intensive course conducted annually for each batch of students. The majority of the students (60%) face writing challenges, while the study reveals that (80%) of the students had no prior English-medium education, and more than (90%) reported that the lack of English proficiency affects their GPA. The findings highlight that students’ English proficiency is significantly influenced by their secondary education. A lack of English language exposure and various linguistic challenges including difficulties in language learning and communication, including grammar, vocabulary and pronunciation further impede their academic progress at the university level. The study uncovered a significant correlation between low English language proficiency and low GPA of students. Conducting motivational English Language programs for secondary learners, improving English language learning methods in schools, facilitating the undergraduates with more English study programs and resources within the university, providing the students with technical glossaries, and improving learner-centered education can be suggested as the main solutions to the problems found.
Keywords: English medium; Challenges; Language proficiency; Secondary education